Impact of individual-specific strength exercises on knee muscle strength and speed performance in speed skaters: a randomised control trial - Kacha, A. R.; Tank, K. (EPJ Web of Conferences, 2026)
Background: Speed skating performance relies heavily on lower limb strength, neuromuscular control, and coordination. Weakness of knee muscles can limit performance and increase the risk of overuse injuries. Individual-specific strengthening of knee flexors and extensors may enhance strength and skating speed, yet evidence in young skaters is limited.